1980
DOI: 10.1017/s004317450002779x
|View full text |Cite
|
Sign up to set email alerts
|

Sicklepod (Cassia obtusifolia) and Coffee Senna (Cassia occidentalis): Geographic Distribution, Germination, and Emergence

Abstract: The distribution of sicklepod (Cassia obtusifoliaL.) and coffee senna (Cassia occidentalisL.) in the United States is similar and both species are increasing as problems within their range. Sicklepod is a problem in 11 southern states and increasing in 12 while coffee senna is a problem in 7 states and increasing in 8 states. Both species germinated over a wide range of temperature. Germination characteristics were similar in the range of 15 to 36 C. Germination of coffee senna was drastically reduced at 39 C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 8 publications
4
63
0
Order By: Relevance
“…Previous studies also have shown that scarification markedly increased germination of seeds of S. marilandica (Mitchell, 1926) and of S. obtusifolia (Creel et al, 1968;Singh, 1968;Teem et al, 1980). Additionally, scarified seeds of S. marilandica and S. obtusifolia germinated equally well in light and darkness (Table 2).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Previous studies also have shown that scarification markedly increased germination of seeds of S. marilandica (Mitchell, 1926) and of S. obtusifolia (Creel et al, 1968;Singh, 1968;Teem et al, 1980). Additionally, scarified seeds of S. marilandica and S. obtusifolia germinated equally well in light and darkness (Table 2).…”
Section: Discussionmentioning
confidence: 52%
“…In their study, no seeds germinated at 15°C, and only a very few germinated at 39°C. Teem et al (1980) reported that the optimum germination temperature for sulfuric acid-scarified seeds of S. obtusifolia was from 24 to 36°C; at 39°C, about 50% of the seeds germinated. Non-scarified seeds of S. marilandica germinated to 0% or to very low percentages over the range of thermoperiods, whereas scarified seeds germinated to high percentages at thermoperiods of 20/10 to 40/25°C (Tables 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…Its center of origin is tropical, but the time and point of entry into the United States is unknown (Brown and Bridges 1989). Teem et al (1980) surveyed weed extension specialists in each of the 50 states to find that sicklepod was troublesome in 11 southern states and increasing in 12 other states. Webster (2001) also identified sicklepod as one of the 10 most 1 Received for publication September 24, 2003, and troublesome weeds of various broadleaf crops in Alabama, Florida, Georgia, Kentucky, Louisiana, North Carolina, South Carolina, Tennessee, and Virginia. Sicklepod has many characteristics that enable it to thrive in a variety of environments.…”
Section: Introductionmentioning
confidence: 99%
“…Senseman and Oliver (1993) showed that sicklepod can produce consistent flower primordia regardless of the environmental field conditions. Sicklepod can grow in temperatures of 18 to 36 C, yet thrives at 30 to 36 C, and at a pH range of 3.2 to 7.9 (Creel et al 1968) and is capable of emerging from a 12.5-cm soil depth (Teem et al 1980). After 2 yr of seed deposition, 5,336 and 2,528 seed/m 2 were found in tillage and no-tillage systems, respectively (Barrapour and Oliver 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although most harvested cereals are mechanically cleaned and selected before being processed, if present Senna occidentalis ( So ) seeds always contaminate the final product, including animal rations, because of their similarity in size and density to crop grains. For this reason many studies have been conducted in order to control the contamination of the crops with these seeds; nevertheless, so far the systems used for the management of this weed have been expensive and not completely effective (Teen et al., 1980; Boyette et al., 1993; Keeton et al., 1996).…”
Section: Introductionmentioning
confidence: 99%